Reductive solidification/stabilization of chromate in municipal solid waste incineration fly ash by ascorbic acid and blast furnace slag. (September 2017) - Zhou, Xian; Zhou, Min; Wu, Xian; Han, Yi; Geng, Junjun; Wang, Teng; Wan, Sha; Hou, Haobo
Abstract: Fly ash is a hazardous byproduct of municipal solid waste incineration (MSWI). Cementitious material that is based on ground-granulated blast furnace slag (GGBFS) has been tested and proposed as a binder to stabilize Pb, Cd, and Zn in MSWI fly ash (FA). Cr, however, still easily leaches from MSWI FA. Different reagents, such as ascorbic acid (VC), NaAlO2, and trisodium salt nonahydrate, were investigated as potential Cr stabilizers. The results of the toxicity characteristic leaching procedure (TCLP) showed that VC significantly improved the stabilization of Cr via the reduction of Cr(VI) to Cr(III). VC, however, could interfere with the hydration process. Most available Cr was transformed into stable Cr forms at the optimum VC content of 2 wt%. Cr leaching was strongly pH dependent and could be represented by a quintic polynomial model. The results of X-ray diffraction and scanning electron microscopy-energy dispersive analysis revealed that hollow spheres in raw FA were partially filled with hydration products, resulting in the dense and homogeneous microstructure of the solidified samples. The crystal structures of C–S–H and ettringite retained Zn and Cr ions. In summary, GGBFS-based cementitious material with the low addition of 2 wt% VC effectively immobilizes Cr-bearing MSWI FA. Graphical abstract: Highlights: Ascorbic acid was used as S/S reagent for Cr reduction in MWSI fly ash. The leaching concentration of Cr is strongly dependent on the pH of the solution. The lowest leaching concentrations of Cr was in the pH range of 6–8. C-S-H and ettringite formed by GGBFS can hold Zn and Cr in its crystal structure.